Copper stabilized bimetallic alloy Cu–Bi by convenient strategy fabrication: A novel Fenton-like and photothermal synergistic antibacterial platform. (15th February 2022) - Ma, Sihan; Luo, Xian; Ran, Guang; Zhou, Zonglang; Xie, Jun; Li, Yipeng; Li, Xingyong; Yan, Jianghua; Cai, Wangyu; Wang, Lin
Abstract: The release of pollutants from bacterial pathogens in air or water, which causes a serious threat to human health and well-being. Traditional antibiotics have exhibited insufficient ability in combating bacteria owing to the emergence of drug-resistant bacteria. Hence, effective antibacterial candidates urgently need to be explored as an alternative for overcoming the antibiotic barrier. It is highly necessary to find an effective stable disinfection system with the nature of environmental-friendly, high activity and stability, convenient synthesis procedure, low energy, cleaner, and low economic consumption. Considering these aspects, optical strategy and chemical treatment bring convenience and advantages in bacterial inactivation. In this work, the bimetallic Cu–Bi alloy was explored using a simple one-pot solvothermal strategy. On the one hand, the bimetallic structure can prevent copper from oxidation to decrease potential secondary pollution activity caused by excessive release of copper ions, and maintain copper's highly biological activity. On the other hand, the as-prepared Cu–Bi alloy was employed to perform antibacterial applications. Hyperthermia is driven by near-infrared light and the introduction of ROS from Cu Fenton-like reaction that can effectively promote the death of bacteria, and perform a better antibacterial ability than that of single Ag + or Cu 2+ release, resulting in the significant growth inhibition of E. coli . Overall, the combination of the multiple disinfection ability of the Cu–Bi alloy, involving highly efficient ROS generation and effective photothermal performance, not only shows the potential in fighting against pathogenic bacteria but also provides an important insight for the exploration of antibacterial platforms based on the bimetallic materials. Highlights: The stabilized bimetallic Cu-Bi alloy is briefly designed using solvothermal method for application in cleaner production. The Cu–Bi combined the advantages of bismuth and copper activity. The closed-circuit loop of the Cu–Bi alloy to perform a satisfying photothermal phenomenon. The Cu–Bi alloy exhibited good synergistic functions in photothermal and chemical antibacterial strategy. The Cu–Bi alloy operated a better bactericidal performance than Ag + and Cu + .